"You know that's a rip-off": policies and practices surrounding micro-enterprises and poverty alleviation in South African township tourism. Issue 12 (1st December 2016) - Koens, Ko; Thomas, Rhodri
ABSTRACT: Supporting the development of small tourism businesses has been seen by policy-makers as a valuable means of alleviating poverty in South African townships. This perspective has been endorsed by several "responsible" tourism businesses and academics. Following a literature review, this paper reports the findings of an empirical study that examined the practices of 80 micro-business owners and the factors that shape their behaviour in two South African townships. In spite of significant visitor numbers, it finds that their narrow social networks, the imbalances of power between them and intermediaries such as travel agencies and tour operators, ideas of Ubuntu and Umona, and complex family and ethnic ties all represent barriers that prevent them from developing their businesses and sharing in the material gains available through tourism. This analysis has important implications for local policy-makers and those advocating responsible tourism. For the former, it suggests a cessation of current initiatives in favour of greater regulation and alternative forms of investment. For the latter, it implies a need to reassess the utility of advocating responsible tourism to consumers in a context where they do not understand the dynamics which fashion what is on offer or the implications of their choices.